(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The project management in construction industry plays a vital role in success of any construction project. Planning is one of the basic preparations needed before starting any project. The most of the construction projects in India are delayed due to improper management and planning. The project planners have to take care of timely delivery by considering all the factors affecting the project management. The construction projects are to be planned according to available resources, manpower, funding, permissions and assurance of timely completion with better quality. Authors have tried presenting the review of various means of construction management and planning by the literature survey carried out on the papers from different countries and the opinions are concluded.